Stability of Three-Dimensional Slurry Trenches with Inclined Ground Surface: A Theoretical Study - Xiao-Fei Jin; Shu-Ting Liang; Xiao-Jun Zhu (Advances in Materials Science and Engineering)
Stability of slurry trenches is an important issue during the construction of the groundwater cutoff walls and diaphragm walls, and thus gradually draws attention. In this paper, a theoretical method for a three-dimensional trench model with an inclined ground was proposed. Based on the Coulomb-type force equilibrium, a safety factor assessing the stability was derived. The results showed that the existing two-dimensional model was conservative compared to the present three-dimensional model; concretely, a greater inclined angle of the inclined ground and trench length decreased the safety factor. This work could be used to assess the trench stability for both 2D and 3D cases with inclined ground surfaces.